Safety and toxicity concerns of orally delivered nanoparticles as drug carriers. (March 2015) - Araújo, Francisca; Shrestha, Neha; Granja, Pedro L; Hirvonen, Jouni; Santos, Hélder A; Sarmento, Bruno
<x xml:space="preserve">Abstract</x> Introduction : The popularity of nanotechnology is increasing and revolutionizing extensively the drug delivery field. Nanoparticles, as carriers for oral delivery of drugs, have been claimed as the perfect candidates to overcome the poor bioavailability of most of the drugs by improving their solubility and/or permeability across biological barriers. However, this is still a promise to be fulfilled. Areas covered : In this review, several nanosystems used as oral drug carriers are described along with their toxicological profiles. A number of nanoparticles based on different types of materials such as polymers, lipids, silica, silicon, carbon and metals are reviewed. Both in vitro and in vivo-based toxicological studies are discussed in this paper. Expert opinion : Toxicological concerns have been raised in the past few years regarding the safety of the developed nanosystems. Assuming that most of the materials used are biocompatible and biodegradable, the toxicity caused by them when formulated into nanoparticles is usually neglected by the scientific community, existing only a few number of studies that approach the toxicity of the nanosystems. This is particularly important, because the materials that composed of the nanoparticles as well as their features such as size, charge and surface properties, will influence their pharmacokinetics after oral administration.